Possibilities of social media in information operations - Kovanda, Petr (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Current conflicts are characterized by the changing environment having a considerable influence on military operations. The armed forces must calculate with civilian factors that are increasingly coming to the forefront in conducting operations. It is no longer enough to defeat the enemy using military power, but necessary to stabilize the area of responsibility and incline thelocal population to be on our side. Influencing the civilian population is conducted mainly by providing information that is disseminated by traditional methods such as radio, television, and print. Dissemination of information is no longer just the domain of the media but comes to the fore via internet communication. Thanks to the development of technologies and especially the availability of Smartphones, social networks are becoming the new phenomena.
Keywords: media społecznościowe; operacje informacyjne; operacje psychologiczne; wpływ